3D laparoscopic treatment of bladder cancer with pelvic multi-organ invasion: a case report and literature review - Chen, Zheng; Deng, Kaifeng; Sun, Luping; Qu, Lijun; Chao, Xinhui; Rao, Jingmin; Hong, Caimmei; Zhuo, Yumin; Lin, Zhichao; Lai, Caiyong (Frontiers in Oncology, 2023)
Introduction Radical cystectomy with dissection of pelvic lymph nodes and urethral diversion is the standard surgical treatment for muscle-invasive non-metastatic bladder cancer. In rare cases where patients with bladder cancer without distant metastasis have pelvic multi-organ invasion, the cancer compresses or invades the ureter and, in severe cases, leads to bilateral upper urinary tract obstruction and renal damage. The treatment recommended by guidelines often cannot improve the patients’ clinical symptoms immediately, and patients cannot complete the treatment owing to severe side effects, resulting in poor survival benefits. Case presentation A 69-year-old woman with facial edema was treated at the First Affiliated Hospital of Jinan University. The serum creatinine and potassium values were 1244 umol/L and 5.86 mmol/L, respectively. Pelvic magnetic resonance and abdominal computed tomography revealed that the bladder tumor had infiltrated the uterus, anterior vaginal wall, rectum, right ureter, right fallopian tube, and right ovary and metastasized to multiple pelvic lymph nodes. Tumor invasion of the right ureter resulted in severe hydronephrosis of the right kidney and loss of function and obstructive symptoms in the left kidney. Four days later, the patient’s creatinine level decreased to 98 u mol/L, the general condition significantly improved, and the patient and family members strongly desired surgical treatment of the tumor. Through a comprehensive preoperative discussion, possible intraoperative and postoperative complications were evaluated. Right nephrectomy, right ureterectomy, total pelvic organ resection, extended pelvic lymph node dissection, and bowel and urinary diversion were conducted under 3D laparoscopy-assisted treatment. The patient was followed-up for 1.5 years and showed good tumor control, self-care, and mental status. Conclusion Minimally invasive surgery is a curative option for patients with bladder cancer with pelvic multi-organ invasion without distant metastasis. Surgeons should strictly control the indications for surgery and warn patients about the occurrence of related post-surgical complications.